Analisis Pasar dan Peluang Usaha Syariah di Pantai Anyer, Banten : Potensi dan Tantangannya - Hafidz Ainur Rofi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Increasing awareness of the halal lifestyle among Muslim tourists worldwide opens up great opportunities for the tourism sector. Muslim tourists look for destinations that are not only beautiful, but also in accordance with Islamic principles. Anyer Beach, as one of the leading tourist destinations in Banten Province, displays beautiful natural views and various attractive tourist facilities. This beach is a favorite destination for domestic and foreign tourists, including Muslim tourists who are looking for a halal tourism experience. Even though Anyer Beach has great potential as a halal tourist destination, this sector is still quite new and not yet fully developed. Therefore, market analysis and opportunities for sharia struggle at Anyer Beach are very crucial to identify potential and challenges in the halal tourism sector.